Respuesta :

Answer:

yes

Step-by-step explanation:

2x−5y=6

Substitute x=3 y=0 into the equation and see if it is true

2(3) -5(0) =6

6 -0 = 6

6=6

This is true so (3,0) is a solution

Lanuel

Answer:

Yes (3, 0) is a solution.

Step-by-step explanation:

From the equation;

2x - 5y = 6

(x, y) = (3, 0)

3 and 0 equals x and y respectively

To test if the ordered pair is a solution to the equation, we would input the respective value of x and y;

2x - 5y = 6

2(3) - 5(0) = 6

6 - 0 = 6

6 = 6 (proof).

ACCESS MORE